Study of reading habits 1989 - Åstorp, Bjuv and Helsingborg - Weibull, Lennart (University of Gothenburg, 1992)
This survey forms part of the research program ´Dagspresskollegiet´. The target group of this survey was the inhabitants of three municipalities in Northwestern Skåne: Åstorp, Bjuv and Helsingborg. Most of the questions are replications of questions asked in previous readership studies, i.e. questions concerning reading habits, subscriptions of papers, reading interests and background variables such as gender, age, education and party preference. The respondent also had to compare the two local papers Helsingborgs Dagblad and Nordvästra Skånes Tidningar with regard to a number of qualities. A battery of questions dealt with the local paper Helsingborgs Dagblad specifically.

This survey forms part of the research program ´Dagspresskollegiet´. The target group of this survey was the inhabitants of three municipalities in Northwestern Skåne: Åstorp, Bjuv and Helsingborg. Most of the questions are replications of questions asked in previous readership studies, i.e. questions concerning reading habits, subscriptions of papers, reading interests and background variables such as gender, age, education and party preference. The respondent also had to compare the two local papers Helsingborgs Dagblad and Nordvästra Skånes Tidningar with regard to a number of qualities. A battery of questions dealt with the local paper Helsingborgs Dagblad specifically.
Läsvanestudien 1989 - Åstorp, Bjuv och Helsingborg
Keywords: internal politics; inrikespolitik; Media; Media; Political behaviour and attitudes; Politiska beteenden och attityder; Leisure, tourism and sport; Fritid, turism och sport; Social Sciences; Samhällsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap